Post-Coloniality and Racial Subjugation in the South Asian Conflict-Affected Chittagong Hill Tracts - Hossain Siddiqui, Muhammad Sazzad (Philosophy and Progress, 2023)
The absence of colonial and post-colonial examinations of the conflict-ravaged Chittagong Hill Tracts (CHT) – a Bangladesh’s distant fringe– warranted me to explore how colonial legacy facilitated the post-colonial statist approach and majoritarian Bengali supremacists’ tendencies to exploit and subjugate the distinct CHT culture. This reconnaissance endeavour finds that the history of extortion of the Chittagong Hill Tracts (CHT)indigenous peoples is a suitable example of racism victims, and thus it examines in the light of the colonial and post-colonial discourses. This explorative study – based on secondary sources of data – finds the very ideas of racism practices, especially identity politics, demographic politics, and women’s subjugation, are prevalent in this postcolonial (and internally colonised) terrain. Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 61-77